Efforts to Improve Students' Learning Montivation in Social Studies Learning with the Lecture and Question and Answer Methods at Mis Hidayatusshalihin Nw Lanji - Rahmawati, Wahidah; Khasanah, Uswatun; Fitrianingsih, Uun; Hasanah, Uswatun; Rosyidah, Vina Nur (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
Learning motivation is an important factor in improving student learning outcomes. This study aims to analyze efforts to improve student learning motivation in Social Sciences (IPS) learning with Community Economic Activities material through lecture and question and answer methods for 5th grade students of MIS Hidayatusshalihin NW Lanji. The lecture method is used to convey basic concepts systematically, while the question and answer method is applied to improve student interaction and understanding of the material. This study uses a qualitative descriptive approach with observation, interview, and questionnaire techniques as data collection instruments. The results of the study indicate that the application of the lecture method accompanied by interactive questions and answers can increase student involvement in learning, strengthen conceptual understanding, and encourage students to be more active in asking and answering questions. In addition, the existence of positive rewards and feedback from teachers contributes to increasing student learning motivation. Thus, the lecture and question and answer method can be an effective strategy in increasing student learning motivation in IPS learning, especially in understanding community economic activities